2023
DOI: 10.1039/d3bm00598d
|View full text |Cite
|
Sign up to set email alerts
|

Matrix stiffness triggers chemoresistance through elevated autophagy in pancreatic ductal adenocarcinoma

Haopeng Pan,
Shajun Zhu,
Tiancheng Gong
et al.

Abstract: Matrix stiffness based on GelMA hydrogel triggers chemoresistance to gemcitabine through autophagy in pancreatic ductal adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 77 publications
1
4
0
Order By: Relevance
“…Increase in hydrogel stiffness changed the sensitivity of breast cancer cells to DOX. A stiffened hydrogel was found to decrease the sensitivity of cells to drug, which is consistent with previous reports [ 23 , 52 , 53 ]. Furthermore, the expression of P-gP mRNA increased when cells were incubated in the agarose hydrogels with DOX, which should be because cancer cells exposing to DOX can stimulate P-gP expression [ 34 ].…”
Section: Resultssupporting
confidence: 92%
“…Increase in hydrogel stiffness changed the sensitivity of breast cancer cells to DOX. A stiffened hydrogel was found to decrease the sensitivity of cells to drug, which is consistent with previous reports [ 23 , 52 , 53 ]. Furthermore, the expression of P-gP mRNA increased when cells were incubated in the agarose hydrogels with DOX, which should be because cancer cells exposing to DOX can stimulate P-gP expression [ 34 ].…”
Section: Resultssupporting
confidence: 92%
“…Furthermore, here we report that PDAC cells with acquired chemoresistance to gemcitabine and paclitaxel adopt an increased contractile behavior as compared to their parental clones. Previous studies mainly focused on investigating PDAC chemoresistance triggered by culturing drug-sensitive cells on substrates with varying stiffness [9,10,38,39]. For instance, Shah and collaborators characterized some mechanical features of PDAC cells with acquired gemcitabine resistance [15], showing a switch to mesenchymal phenotype and an increased migratory/invasive potential.…”
Section: Discussionmentioning
confidence: 99%
“…The cell line SUIT-2.028 has an epithelial-like phenotype, while PATU-T and SUIT-2.007 were representative of the mesenchymal phenotype. Given that no significant difference was observed between the intermediate stiffness values (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47), and that the stiffest value investigated (142 kPa) has less physiological relevance for PDAC, in what follows we proceeded in comparing the soft and stiff substrates of 11 and 47 kPa only. We first confirmed, as for the non-resistant cells, that PDAC chemoresistant cells had variable cell spreading area, and that the mean force per pillar was a faithful measure of traction forces (see Supplemental Table 4 and Supplemental Figure 4).…”
Section: Pdac Cells Force Generation Is Stiffness-dependentmentioning
confidence: 99%
“…Our previous studies have shown that a stiff hydrogel can change the sensitivity of tumor cells to chemotherapy drugs, and the potential mechanism maybe changes in the level of autophagy. 11 It has also been suggested that changes in matrix stiffness have been shown to activate intracellular mechanical signal transduction pathways, which in turn affect the nuclear localization of YAP and ultimately regulate the development of different organs. 7 Moreover, YAP signaling has been shown to have different roles at different stages of pancreatic β-cell differentiation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Thus far, many studies have confirmed that in vitro simulation of the matrix stiffness of the ECM can activate organ development signals in vivo, thereby altering cell differentiation or drug sensitivity. Our previous studies have shown that a stiff hydrogel can change the sensitivity of tumor cells to chemotherapy drugs, and the potential mechanism maybe changes in the level of autophagy . It has also been suggested that changes in matrix stiffness have been shown to activate intracellular mechanical signal transduction pathways, which in turn affect the nuclear localization of YAP and ultimately regulate the development of different organs .…”
Section: Introductionmentioning
confidence: 99%